Importance of winter rape for small rodents - M. Heroldová; J. Zejda; M. Zapletal; D. Obdržálková; E. Jánová; J. Bryja; E. Tkadlec (Plant, Soil and Environment, 2004)
Winter rape stands are important habitat for the common vole (Microtus arvalis) and the pygmy field mouse (Apodemus microps). In autumn, the common vole is dominant in this habitat (D = 75%) and reproduces in it (17% of population). This species also dominates the small mammal community of winter rape in early spring (D = 87%), and its reproduction begins in this habitat early; under suitable meteorological conditions 44% of the population of common vole reproduce in March. Analyses of the spring and autumn diet of M. arvalis in winter rape have shown that green leaves of this species form the dominant component of its diet. During the period when the rape crop is ripening, the population abundance of the common vole decreases as green food at ground level decreases. The pygmy field mouse (A. microps) has a contrasting response to winter rape, and it is almost absent from the rape crop from autumn to late spring. However, when winter rapeseeds begun to ripen, the pygmy field mouse concentration in this habitat is in large numbers (dominance D = 76%) and rapeseeds dominate its diet (v% = 72). After the harvest of winter rape, when shed seeds begin to grow, both small mammal species live for some weeks on rape plots.